Pyrotechnic Delay Compositions Based on BaO2: Not as “Green” as Expected - Kinga Lysien; Klaudia Szatan; Konrad Szydlo; Mateusz Polis; Marcin Procek; Agnieszka Stolarczyk; Tomasz Jarosz (Molecules, 2023)
The aims of this study were to investigate the potential of using barium peroxide as an environmentally friendly oxidising agent, to evaluate the composition of the combustion products of the developed pyrotechnic delay compositions (PDCs) and to provide information about the impact of the utilised metallic fuel (Mg, Al, Fe or Cu) on the properties of those PDCs. The PDCs exhibited acceptable friction and impact sensitivity values. This allowed conducting further experiments, e.g., determining the linear combustion velocity of the PDCs as a function of oxygen balance (OB). Based on the composition of the post-combustion residues, determined by Raman spectroscopy and SEM-EDS, an initial mechanism for the combustion of the developed PDCs was proposed.